The Radical Transformation Of Company Law: Global Trends And Local Initiatives - Farrar, John H (Journal of Malaysian and Comparative Law, 2006)
This is an edited version of the Inaugural Lecture of the Tun Ismail Mohamed Ali Foundation Chair delivered at Nikko Hotel, Kuala Lumpur on 18 May 2007.